Aid and poverty reduction: comparing China and France's aid policies and projects in Guinea - Diakité, Ansoumane Douty (University of Saint Joseph, 2016)
The purpose of this research is to analyse the nexus between foreign aid and poverty reduction. In this research, aid provided by traditional and (re)emerging donors, China and France, was compared to understand their strategies toward poverty reduction and the impact of their aid in improving the conditions of their beneficiaries. Guinea, a Least Developed Country, was used as unit of comparison and assessment. Qualitative research methodology was used to collect data about the two aid donors, China and France. Among other research tools used, there are documents’ analysis (official documents from donors and recipients, declarations, scholarly works, media articles, etc.), interviews with various stakeholders, site visits and observation. As for main findings, this research found similarities and differences between China and France’s aid strategies in general and in Guinea in particular. There are similarities in the ways they integrate poverty reduction into their aid policies, motives and partly in their geographical and sectoral allocation systems. In terms of differences, they use different instruments and conditions to deliver their aid for poverty reduction. Regarding the impact of their aid, both donors have to some extent contributed to improving the access of the poor population in Guinea to basic services such as education, health, water and sanitation, etc. Finally, contrary to those who have denied the importance of foreign aid as a financial tool to reduce poverty, this research posits that aid is still a relevant tool to address poverty. However, more work needs to be done at donor, recipient and direct beneficiaries’ levels to ensure its effectiveness. On the other hand, it posits that the divide between traditional and (re)-emerging donors is becoming blurred as their strategies to address poverty are becoming increasingly alike
Keywords: Thesis and Dissertations PhD in Government Studies (D-GS); University of Saint Joseph

Macau fashion industry in the 21st Century: a global studies perspective on Asia-Europe cultural exchange - Dias Cardoso, Ana Cláduia (University of Saint Joseph, 2017)
Macau is a dynamic city with a unique blend of Eastern and Western cultures, which has become a well-known travel destination. Macau is not only home to the casinos, but also a shopping paradise, where we can find international luxury brands and local designer brands. The local fashion industry has a strong follower base, taking a different route than that of the Textile and Garment Industry in the 1980s. Nowadays, the local Fashion Industry is not only focused on production, but more on the design and creativity. Macau is a city rooted in the casino industry, having shifted from an industrial economy into a service-based one. This study aims to assess the relations between Asia and Europe with regard to their impact on the creative process of local fashion designers, to understand how local designers balance between market, creativity and aesthetics. Also, it is important to understand how Macau government supports local brands such as: “Made in Macau”. In order to accomplish our goal, several academic areas will be addressed, such as fashion design and the cultural and creative industries in their broad sense, (aesthetics, history, creativity, identity, economy, ergonomics, cognition, and social value). A mix of quantitative and qualitative methods have been used, including questionnaires, open-ended interviews, case-study research, ethnographic methods, historical research and visual methodologies. In the following chapters, this studies will describe mainly the Macau fashion industry in a globalized era and the multiculturalism’s influence on the local fashion designer’s collections
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; Thesis and Dissertations PhD in Global Studies (D-GLS); University of Saint Joseph

Accounting in Macau: A Historical Perspective from 1970s until 2008 - Lam, Ching Chi (University of Saint Joseph, 2011)
The current research study embraced the objectives to investigate the transformation of accounting in Macau from the first set of accounting legislations in 1970s, through the first set of accounting standards in 1983, until a year after the first application of international accounting standards, by 2008. From the transformation, the role taken by accounting in the economy and the factors that have influenced the transformation were intended to identify. Through the historical picture, findings have supported and expanded the theoretical concepts that accounting was taking both active and passive roles in the economy. Furthermore, they also supported the theoretical concepts that culture, economic environment, political environment and education influenced the transformation of accounting. The objectives have been structured through three research issues identified from the analysis of past literatures. Five qualitative and quantitative research studies have been carried out, using primary and secondary data from both primary and secondary sources. In-depth interviews on 13 representative respondents of the government, the profession, the industry and the academia, directly or in-directly related with accounting have been done. A case study on a company doing business in Macau since 1970s was included to enrich, supplement and evaluate the findings on the accounting practice of Macau. Based on the findings, a model has been constructed that represented the interaction between accounting and the different factors of the economy. Contributions from the research findings have enriched the research literatures on the area of accounting history. Implications from the findings have generated better insights for the business and economic histories of Macau
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; Thesis and Dissertations PhD in Business Administration (D-BA); University of Saint Joseph